Membangun Kemandirian Ekonomi Melalui Pembuatan Sabun Cuci Piring dan Deterjen “DIY” - Darman Safe’i; Noviansyah Noviansyah; Hilmi Wiranata; Lusiana Lusiana; Yesa Cecilia (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2025)
Activities to develop economic independence through making DIY dishwashing soap and detergent were carried out in Marga Bakti January 2025 as an effort to improve community skills in utilizing local resources. This program aims to provide practical training that can be applied independently by the community to create small business opportunities based on household needs. Implementation methods include theoretical explanations, manufacturing demonstrations, and group practice, accompanied by intensive mentoring. The results of the activity show that participants are able to produce quality soap and detergent independently, which has the potential to increase family income while reducing dependence on commercial products. This program is expected to be the first step in building a sustainable and community-based economy in Marga Bakti Village.